Desenvolvimento sustentável e jardim sensorial por meio da aprendizagem baseada em projetos - ABP - Silva, Jander Ramires Rodrigues (Brasil, 2025)
Sustainable Development (SD) is based on three pillars: Environmental, Economic and Social. Nowadays, with technological advances and innovative production processes, how are students learning this concept? For this research, a Sensory Garden (JS) already implemented at the Federal Institute of Education, Science and Technology of Amazonas, Campus Manaus Centro, was used for students of the 1st year of High School in the class of the Technical Course in Chemistry, where it established the following problem question: “How to develop activities for teaching Sustainable Development from a Sensory Garden?”. The general objective was to investigate the contributions of a JS to the understanding of Sustainable Development and its Objectives, to students of the 1st year of high school. And as specific objectives, to propose Project-Based Learning (PBL) as a teaching methodology to approach SD based on the UN's 2030 Agenda, through the JS. And in addition, verify the potential of using JS as a didactic resource and non-formal teaching space, for the promotion of DS and its Objectives. The research approach was qualitative and the teaching method adopted was based on PBL. The insertion of the theme was aligned with the National Common Curricular Base, in the context of competences and abilities to be developed by the students, as well as the Transversal Contemporary Themes. The ABP project was developed in the form of a workshop lasting three hours (3h) presenting the JS as a non-formal teaching space, in order to promote students' awareness of environmental issues. After the methodological process, it was observed that the students were able to relate the SD to the JS, through observation and analysis of the Sustainable Development Goals (SDGs) that are part of the 2030 Agenda, presenting characteristics of the concepts addressed during the Workshop “Looking for Sustainable Development. And in the socialization of the artifacts elaborated by the groups, it was clear that the students were able to answer the driving question worked on in the structure of the PBL Workshop in Table 2.